دور المنتج الأخضر في التّأثير على اتّجاهات المستهلكين للشّراء دراسة ميدانيّة على المنشآت الصّناعية في السّاحل السّوري (Journal of Hama University, 2024)
This research aimed to study the role of green product in influencing consumers' attitudes to purchase in the industrial institutions operating in the Syrian coast, on a sample of consumers of products. The analytical description and data analysis approach was relied on using SPSS program. The questionnaire was organized based on studies and literature reviews, and 445 questionnaires were distributed to an appropriate sample of consumers to test the research hypotheses. After conducting analysis the study data and testing its hypotheses, a set of results were reached, the most prominent is that there is strong and significant relationship between the green product and consumers' attitudes to purchase in industrial institutions operating on the Syrian coast, and that the consumers' attitudes towards green products are positive. The researcher also recommended a number of recommendation, the most prominent of which was the need to strengthen the concept of environmental dimension and developing marketing strategies by the institutions studied by paying attention to environmentally friendly products and to meet consumers' needs and expectations due to the importance purchase these products in positively affecting the consumers' attitudes or reluctance to purchase.